Cupular growth of embryonic free neuromasts in the willow shiner, Gnathopogon elongatus caerulescens, and the pattern in the changes in cupular length after hatching - Mukai, Yukinori (Springer Tokyo, 1995)
This study examined the length of embryonic cupulae of willow shiner. Before hatching, embryos had long cupulae, but after hatching the cupulae became short length.